Impact of Ownership Structure on Financial Performance of Listed Companies on the Hanoi Stock Exchange - Trinh, Ngo Tuyet (International Journal of Scientific Research and Management (IJSRM), 2024)
This essay reviews studies on the types and levels of fragmentation in firm ownership, focusing on how ownership structure impacts firm performance. Using a property rights framework, the essay integrates sociological, organizational, legal, and economic research that explores the relationship between ownership organization and firm performance. Agency theorists typically assume that shareholders are uniform in nature, and that their impact on firm performance correlates directly with their equity stakes. However, empirical studies based on this assumption have not produced clear evidence. Class analysis perspectives view these mixed results as evidence that firms, regardless of ownership structure, primarily serve the capitalist class. An alternative view suggests that shareholders are not homogeneous, and certain types of shareholders use their formal authority, social influence, and expertise to capture property rights, thereby exerting significant influence on firm performance. The impact of various owners may vary based on industry characteristics, and the essay reviews literature supporting a contingency theory of ownership structure.